Orfelia gruevi spec. nov. from Bulgaria (Diptera: Sciaroidea: Keroplatidae) - Bechev, Dimitar (Acta entomologica slovenica (Ljubljana), 2002)
A new species of the genus Orfelia A. Costa from the Northern part of the Bulgarian Black Sea area is described.
Keywords: Bolgarija; Bulgaria; Diptera; dvokrilci; zoogeografija